Measurement of Length of Styloid Process by Orthopantomography - Sharma, BR; Singh, S; Timilsina, M; Sharma, P; Sharma, K (Journal of Gandaki Medical College-Nepal, 2019)
Background: Styloid process (SP) is an anatomical structure whose elongation is not well understood. Proper clinical and radiological assessment is needed to detect an elongated SP. Anatomical variation is also common. SP is said to be elongated if longer than 30 mm. Orthopantomogram (OPG) is also an imaging modality by which we can view SP. Objective: The objective of this study was to assess the SP on OPG and identify eagle syndrome. Materials and Methods: The study was conducted on archived OPG radiographs available in the Department of Oral Radiology, Gandaki Medical College Teaching hospital and Research Centre. These radiographs were from patients who were subjected to radiographic examination for other dental problems. The length of SP was measured on both sides using the measurement tool bars on the accompanying analysis software. Results: Average length of SP on males was 26.5 mm ±14.4 mm in right and 25.5 mm ±6.19 mm in left; and on females was 23.78 mm ±5.93 mm on right and 24.7 mm ±10.44 mm in left. Elongated SP was more on males compared to females. Elongated styloid process (ESP) was more prevalent in 21 - 30 years of age group, similarly unilateral and bilateral elongation was also predominant on males compared to females. Conclusion: OPG is also useful for detection of an ESP in patients with or without symptoms and helps to avoid misdiagnosis of tonsillar pain or pain of dental, pharyngeal or muscular origin as well as Eagle syndrome (ES).